Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/s00114-006-0089-y
|View full text |Cite
|
Sign up to set email alerts
|

Larval salivary glands are a source of primer and releaser pheromone in honey bee (Apis mellifera L.)

Abstract: A brood pheromone identified in honeybee larvae has primer and releaser pheromone effects on adult bees. Using gas chromatography-mass spectrometry (GC-MS) to evaluate fatty acid esters--the pheromonal compounds--in different parts of the larvae, we have localized the source of the esters as the larval salivary glands. A histochemical study describes the glands and confirms the presence of lipids in the glands. Epithelial cells of the gland likely secrete the fatty acids into the lumen of the gland. These resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…This proposition builds on previous work by Omholt (Omholt, 1988), who suggested that the nurse load of young honeybee workers affects longevity: a low nurse load can increase lifespan whereas a high nurse load has the opposite effect. In addition to consuming colony resources, however, larval brood secrete a primer brood pheromone, a blend of 10 fatty acid methyl and ethyl esters (Le Conte et al, 1994) produced by the salivary glands (Le Conte et al, 2006). This pheromone affects worker brain gene expression (Alaux et al, 2009), gland physiology (Pankiw et al, 2008) and behavior (Pankiw, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This proposition builds on previous work by Omholt (Omholt, 1988), who suggested that the nurse load of young honeybee workers affects longevity: a low nurse load can increase lifespan whereas a high nurse load has the opposite effect. In addition to consuming colony resources, however, larval brood secrete a primer brood pheromone, a blend of 10 fatty acid methyl and ethyl esters (Le Conte et al, 1994) produced by the salivary glands (Le Conte et al, 2006). This pheromone affects worker brain gene expression (Alaux et al, 2009), gland physiology (Pankiw et al, 2008) and behavior (Pankiw, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Two examples of releaser pheromones in termites are the trail pheromone (Z,Z,E)-3,6,8-dodecatrien-1-ol (Matsumura, 1968) and the phagostimulatory pheromone hydroquinone (Reinhard et al, 2002). Three examples of primer pheromones from the honey bee are worker behavioral maturation inhibitory pheromone (ethyl oleate; Leoncini et al, 2004), brood pheromone (fatty acid esters; LeConte et al, 2006), and queen mandibular pheromone (5 carboxylate and aromatic components; Grozinger et al, 2007). Although no primer pheromones have been identified in termites, JH has been proposed as a possible termite primer pheromone (Henderson, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The esters are present in different amounts and proportions as a function of caste and larval age . Thus, nurses can recognize the various needs of larvae and provide them with optimal care (Le Conte et al, 2006). Four esters, methyl linolenate, methyl linoleate, methyl oleate, and methyl palmitate, induce the worker bees to cap the cell with a thin cover of wax .…”
Section: Interactions Between Adults and Broodmentioning
confidence: 99%
“…They found that methyl stearate increases the acceptance of the queen cells, methyl linoleate enhances the amount of royal jelly deposited by the worker, and methyl palmitate increases the weight of the larvae. In addition to releaser effects on various aspects of brood care, BP also has primer effects (Le Conte et al, 2001Conte et al, , 2006. Methyl palmitate and ethyl oleate increase the activity of the hypopharyngeal glands, which produce proteinaceous material that is fed by nurse bees to larvae (Mohammedi et al, 1996;Le Conte et al, 2001).…”
Section: Interactions Between Adults and Broodmentioning
confidence: 99%